Sudden death in paediatrics as a traumatic experience for critical care nurses - Lima, Lígia; Gonçalves, Sandra; Pinto, Cândida (My University, 2018)
Research shows that nurses working in critical care units and in particular, paediatric units, are at risk of developing symptoms of secondary traumatic stress (STS). However, little attention has been given to this phenomenon when associated with situations of sudden death in paediatrics.
Keywords: Critical care •; Sudden death; Paediatric nursing; Emotional impact; Secondary traumatic stress; Madeira Island; Portugal